Implementasi Filsafat Pendidikan Konstruktivisme terhadap Pembelajaran di Sekolah - agung prasetyo (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
Educational Philosophy Constructivism is a philosophy which assumes that the knowledge possessed by humans is the formation of humans themselves. Human knowledge can be formed through the environment, experience, phenomena, and also interactions with an object. By doing this, humans will gain knowledge so that it will be useful for their lives. It is very suitable for the philosophy of constructivism education to be used in learning in schools, because by using this philosophy, educators and students work together. The method used is the library method to obtain information and online class observations.